2020
DOI: 10.3906/elk-1809-190
|View full text |Cite
|
Sign up to set email alerts
|

Consumer loans’ first payment default detection: a predictive model

Abstract: A default loan (also called nonperforming loan) occurs when there is a failure to meet bank conditions and repayment cannot be made in accordance with the terms of the loan which has reached its maturity. In this study, we provide a predictive analysis of the consumer behavior concerning a loan's first payment default (FPD) using a real dataset of consumer loans with approximately 600,000 records from a bank. We use logistic regression, naive Bayes, support vector machine, and random forest on oversampled and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The two most widely used classification models are the decision tree model (Zhou et al, 2021) and naive Bayesian model (NBM; Yager, 2006). The first payment default (FPD) loans prediction is solved by the NB (Koç & Sevgi̇li̇, 2020) K-Nearest Neighbor (KNN) not only applies to the consumer credit risk (Kruppa et al, 2013) but also it can apply in bank loan default prediction (Arora & Kaur 2020; Kou et al, 2014). Consequently, it can be concluded that KNN has a great prospect in predicting credit default.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The two most widely used classification models are the decision tree model (Zhou et al, 2021) and naive Bayesian model (NBM; Yager, 2006). The first payment default (FPD) loans prediction is solved by the NB (Koç & Sevgi̇li̇, 2020) K-Nearest Neighbor (KNN) not only applies to the consumer credit risk (Kruppa et al, 2013) but also it can apply in bank loan default prediction (Arora & Kaur 2020; Kou et al, 2014). Consequently, it can be concluded that KNN has a great prospect in predicting credit default.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A customer defaults when he or she is unable to meet loan terms, resulting in non-repayment of a loan that has reached maturity [1]. When a consumer misses his loan repayment requirements by one or two instalments, delinquency sets in and ultimately leads to a default.…”
Section: Introductionmentioning
confidence: 99%